Dziewiętnastowieczne górnośląskie protokoły sądu rozjemczego jako podstawa badań językowych = Upper Siliesian village courtroom protocol in 19th century as a distinct type of legal text - Iżykowska, Małgorzata; Starczewska-Wojnar, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article proves, that under the circumstances of a foreign nationality in Silesia in 19th century, the Polish courtroom protocol was formed as a distinct type of a legal text. It was based on German model, which was required by the official administration. It included fundamental linguistic determinants of a protocol. The basis for this thesis comes from numerous Polish protocols, preserved in village courts protocol books from Strzelce County, currently stored in Polish National Archive in Opole.
Keywords: genologia lingwistyczna; gatunek mowy; Śląsk; protokół sądowy; 19 w.; linguistic genology; speach genre; Silesia; courtroom protocol; 19th century